Development of a STEAM Learning Model to Stimulate Creative Thinking Skills in Early Childhood - Rabitah Hanum Hasibuan; Veryawan Veryawan; Masganti Sit; Anita Yus (Journal of Childhood Development, 2026)
STEAM education is an innovation designed to address the challenges of the industrial revolution; as such, teachers utilize various media to support learning. This study aims to develop a STEAM (Science, Technology, Engineering, Art, and Mathematics) learning model specifically designed to stimulate creative thinking skills in early childhood in Binjai City, North Sumatra. Creative thinking skills are essential 21st-century competencies that need to be stimulated from an early age; however, a significant gap between the need for creativity development and conventional learning approaches is still evident in various early childhood education institutions. The research method used is Research and Development (R&D) employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 60 children aged 4–6 years spread across four early childhood education institutions in Binjai City, selected through purposive sampling. Data collection instruments included observation sheets, interview guidelines, and a creative thinking assessment rubric. The results showed that the developed STEAM learning model met the criteria for validity (subject matter expert score of 87.5% and media expert score of 84.3%), practicality (teacher response score of 89.2%), and effectiveness in enhancing children’s creative thinking skills (gain score of 0.68, classified as moderate-high). There was a significant difference in children’s creative thinking abilities before and after the implementation of the model (t=8.47; p<0.001).